1976
DOI: 10.1073/pnas.73.11.4190
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of a viral protein as a diagnostic signal for the presence of tumor : the murine mammary tumor model.

Abstract: We used the mouse mammary tumor and its associated virus (murine mammary tumor virus) to examine the possibility of using'plasdia levels of a viral protein (gp52, the glycoprotein of 52,000 molecular weight) as a diagnostic indicator of the presence of a solid tumor. The following features have emerged from our studies: (a) tumor-bearing animals show markedly elevated (100-1000 ng/ml) plasma levels of gp52 and the mean concentration increases with tumor size; (b) mammary tumor tissues located outside the mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…This expectation is supported by experiments with the murine model, which demonstrated that plasma levels of gp52 provide accurate diagnostic (11) and prognostic (12) information on mammary tumors.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…This expectation is supported by experiments with the murine model, which demonstrated that plasma levels of gp52 provide accurate diagnostic (11) and prognostic (12) information on mammary tumors.…”
supporting
confidence: 49%
“…We wished to examine the antigenic relationship between the particles produced by T47D clones 8 and 11 and MMTV. We have report- ed previously the specific localization of an antigen related to the major MMTV envelope protein, gp52, in human breast tumors (8) and similar staining has been observed in T47D clone 8 and 11 cells (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of detectable amounts of p28 in sera containing gP47 and tested in the presence of detergents confirms that gP47 is not virion-bound in blood (Ritzi et al 1976;Arthur et al I978b). Shedding from the plasma membrane of infected cells appears as a probable mechanism for gP47 production (Van Blitterswijk et al I975;Calafat et al I976).…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown (23)(24)(25) The costs of publication of this article were defrayed in part by the payment of page charges from funds made available to support the research which is the subject of the article. This article must therefore be hereby marked "advertisement" in accordance with 18 U. S. C §1734 solely to indicate this fact.…”
mentioning
confidence: 99%